Translation Strategies of Security an Life Safety Texts - Kiyko, Svitlana (My University, 2022)
The article discusses general translation strategies such as literal translation, borrowing, calquing, equivalence, transposition, modulation, adaptation, expansion, contraction, generalizing, particularizing as well as compensation and restructuring and describes how they can be used when translating texts of security and life safety. The author looks at how to formulate a translation brief and what type of information it should contain. Some of the specific strategic problems a translator might encounter in texts of security and life safety are described as well as some of the strategies a translator use to deal with them are explored. Using a corpus of 500 risk and safety phrases, we compared the use of various translation strategies in English texts and their Ukrainian translations and found that in risk and safety phrases, literal translation occurs more frequently than other strategies such as transposition, modulation, addition or adaptation. Nevertheless, even though literal translation may propor tionally see more use in technical texts, it is by no means the most important strategy, nor does it represent the main tool in a translator's toolbox.
Keywords: translation, safety and risk phrases, literal translation, borrowing, calquing, recategorization, modulation, adaptation